Perosomus elumbis in an Aberdeen Angus calf associated with intrauterine infection with BVDV-1a - Ana Laura Vildoza; Carlos Omar Schild; Leticia Maya; Rodney Colina; Fabiana Marques Boabaid; Florencia Buroni; Karina Cresci; Franklin Riet-Correa; Luiz Gustavo Schneider Oliveira (Ciência Rural)
ABSTRACT: In a beef cattle breeding farm located in northern Uruguay, an Aberdeen Angus calf was born with complex anomalies. The offspring was sired by one of the bulls of the farm. The calf died shortly after birth, displaying multiple malformations at external examination, including agenesis of the lumbar, sacral and coccygeal vertebrae and spinal cord and arthrogryposis of both pelvic limbs, characteristic of perosomus elumbis (PE). At necropsy there was also brachygnathia and muscle atrophy of the pelvic limbs, along with underdeveloped small intestines, atresia ani, ectopia of the left kidney and hypoplasia of the contralateral, testicular fusion and cryptorchidism. Molecular studies of the fetal tissues revealed infection with Bovine Viral Diarrhea Virus (BVDV), an agent known for causing different malformations in cattle.